The Relationship between EVA, MVA and Dividend Paid - An Empirical Study - Ramana Reddy, N. R. V.; Rajesh, M. (Indian Journal of Finance, 2008)
In a global economy of highly competitive environments and transfer of funds, companies are managed in terms of value to the suppliers of the capital i.e., shareholders. Like raw materials and labour, financial capital is also a scarce resource which should be allocated and invested with care and managed with skill. It is therefore important for the investors and management to know with a reasonable measure of accuracy, whether a business enterprise is creating or destroying the value of business. In this direction a number of studies have been conducted on EVA (Economic Value Added) and MVA (Market Value Added).